Sistema de segurança para prevenção e recuperação de roubo de motocicleta - Máximo, Jonas Bezerra da Costa (2022)
Transport plays a key role in the daily life of the population, but the alarming violence of cities forces citizens to be alert to dangers. Motorcycle theft is a major contributor to the increase in violence over the years. Faced with this reality, it was proposed with this work the development of a security system for the prevention and recovery of motorcycle theft in a quick, easy and safe way. The user will be able to control the operation of the motorcycle remotely through a global system for mobile communications and make it impossible to operate the vehicle through the relay that will be connected to the electrical part of the motorcycle, also having access to the location of the vehicle in real time through the locator positioning system. global, in order to facilitate the recovery of the vehicle in case of theft or theft